Book Review of "Encyclopedia of Applied Ethics (2nd ed.)" - Pettifor, Jean L. (Canadian Journal of Counselling and Psychotherapy, 2012)
The Encyclopedia of Applied Ethics presents short articles on a wide range of topics related to ethics. The second edition (2012) includes issues that have become more significant since the first edition was published in 1998. The articles generally include historical roots, theories, current status, unresolved issues, and considerations for the future. Professional ethics as a subheading of Applied Ethics is not covered sufficiently to guide busy practitioners to resolve ethical dilemmas that they encounter in practice.